1998
DOI: 10.1016/s0092-8674(00)80945-9
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Trisphosphate Mediates a RAS-Independent Response to LET-23 Receptor Tyrosine Kinase Activation in C. elegans

Abstract: Activity of LET-23, the C. elegans homolog of the epidermal growth factor receptor, is required in multiple tissues. RAS activation is necessary and sufficient for certain LET-23 functions. We show that an inositol trisphosphate receptor can act as a RAS-independent, tissue-specific positive effector of LET-23. Moreover, an inositol trisphosphate kinase negatively regulates this transduction pathway. Signals transduced by LET-23 control ovulation through changes in spermathecal dilation, possibly dependent upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
256
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(263 citation statements)
references
References 56 publications
5
256
1
1
Order By: Relevance
“…Substitution of the equivalent residue in the mouse type 1 receptor, R441, by glutamine results in a twofold increase in binding (Yoshikawa et al, 1996), whereas conversion to cysteine produces a fivefold increase in affinity (Hirota, personal communication). This substitution is identical to that found in the gain-of-function allele, itr-1 (sy290) (Clandinin et al, 1998).We confirmed that the IP 3 sponge constructs showed the predicted binding to IP 3 in vitro, by using GST fusion proteins of these binding domains. As Figure 1B shows, the wild-type sponge exhibits properties identical to those reported previously for the ITR-1 IP 3 binding domain (Baylis et al, 1999), whereas the super-sponge construct exhibits an approximately twofold increase in affinity.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…Substitution of the equivalent residue in the mouse type 1 receptor, R441, by glutamine results in a twofold increase in binding (Yoshikawa et al, 1996), whereas conversion to cysteine produces a fivefold increase in affinity (Hirota, personal communication). This substitution is identical to that found in the gain-of-function allele, itr-1 (sy290) (Clandinin et al, 1998).We confirmed that the IP 3 sponge constructs showed the predicted binding to IP 3 in vitro, by using GST fusion proteins of these binding domains. As Figure 1B shows, the wild-type sponge exhibits properties identical to those reported previously for the ITR-1 IP 3 binding domain (Baylis et al, 1999), whereas the super-sponge construct exhibits an approximately twofold increase in affinity.…”
supporting
confidence: 78%
“…Substitution of the equivalent residue in the mouse type 1 receptor, R441, by glutamine results in a twofold increase in binding (Yoshikawa et al, 1996), whereas conversion to cysteine produces a fivefold increase in affinity (Hirota, personal communication). This substitution is identical to that found in the gain-of-function allele, itr-1 (sy290) (Clandinin et al, 1998).…”
Section: Molecular Biology Of the Cell 1330supporting
confidence: 66%
See 2 more Smart Citations
“…The rrf-1 mutants are defective with RNAi in the somatic cells but not in the germ cells (Sijen et al, 2001). Thus, if function of an RNAi target is important in the somatic gonad (either sheath contraction [McCarter et al, 1997] or spermathecal dilation [Clandinin et al, 1998;Aono et al, 2004]), ovulation will be defective in wild-type but normal in the rrf-1 background.…”
Section: Roles Of the Myofibrillar Components In Ovulationmentioning
confidence: 99%